Intraspecific differences of section on root head of siler (Saposhnikovia divariacata (Turcz.) Schischkin) in Mongolia - Gombo Oyungerel; Tsambaa Battseren; Jukov Azzaya; Narantsetseg Amartuvshin; Munkhtur Davaagerel (Mongolian Journal of Biological Sciences)
Present study reveals intraspecific differences of root head section of Saposhnikovia divaricata and explain controlling factors. Root head section have divided into three categories and compared to the factors of geography, climate, fire and human activities. Clearly recognized section dominantly recorded in Dornod and Selenge-Tuv-Arkhangai provinces but it showed lower percentage in Khentii and Sukhbaatar. Within the administrative province, it was higher in Bayan-Uul, Sergelen, Dashbalbar and Tsagaan-Ovoo sites, Dornod province; in Dadal, Norovlin and Bayan-Khutag sites, Khentii province and Shaamar, Zuunduren and Altanbulag, Selenge province. The percentage of clearly recognized section was higher with drought events during early summer and lower aridity index, burning and in pasturelands. It was higher on wild roots of S. divaricata than on cultivated ones. Percentage of poorly recognized section was higher in Zuunkharaa, Nomgon and Siakhan sites, Selenge province while that of not-sectioned root head was higher on cultivated roots. The results of our study suggest that clearly and poorly recognized sections on root head of S.divaricata is morphological signs of larger and smaller amounts of storage but not-sectioned root head is of smallest amount. The clearly recognized section can be changed to poorly recognized section and/or not-sectioned roots, caused by coldness, strong fire frequency, trampling and/or gathering and cultivation.